International travellers entering or returning to Canada, by type of transport - Statistics Canada (Government of Canada, 2018)
This table contains 11559 series, with data for years 1972 - 2017 (not all combinations necessarily have data for all years). This table contains data described by the following dimensions (Not all combinations are available): Geography (273 items: Canada; Newfoundland and Labrador; Argentia, Newfoundland and Labrador; Botwood, Newfoundland and Labrador; ...); Traveller characteristics (91 items: Total international travellers; Total non-resident travellers; United States residents entering Canada; United States residents entering Canada, automobile; ...).